The Effect of Green Innovation on Organizational Performance: Role of Enterprise Risk Management As A Mediation Variable - Dahlan, Dahlan; Nurhayati, Mafizatun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The purpose of this study was to examine and determine the effect Enterprise Risk Management (ERM) on Organizational Performance at PT Armada in 2022. Testing the effect of implementing ERM and Green Innovation, as well as the mediation function of Enterprize Risk Management. towards Green Innovation towards the company's organizational performance. The population in this study were all employees at PT Armada. Data were collected by questionnaires according to the list of questions and study documentation. This study uses PLS-SEM with the help of data processing using the SmartPLS 3 application software. The results show that the implementation of Enterprize Risk Management (ERM) affects Organizational Performance, Green innovation affects ERM, green innovation does not affect organizational performance, green innovation through enterprize risk management mediation affects organizational performance indirectly.